2014
DOI: 10.1093/cid/ciu1173
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Colonization and Infection by Klebsiella pneumoniae Carbapenemase-Producing Enterobacteriaceae in Long-term Acute-Care Hospitals

Abstract: A bundled intervention was associated with clinically important and statistically significant reductions in KPC colonization, KPC infection, all-cause bacteremia, and blood culture contamination in a high-risk LTACH population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
182
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(192 citation statements)
references
References 30 publications
7
182
0
1
Order By: Relevance
“…Hayden and colleagues demonstrated that the use of an infection prevention bundle that included chlorhexidine bathing and strict isolation practices in a high-CRE-burden LTACH was able to significantly reduce the rates of both new CRE acquisitions and bacteremia cases (13). Computer model estimates suggest that a coordinated regional response, compared to individual hospital actions, has the potential to reduce or even eliminate CRE transmission (10,11).…”
mentioning
confidence: 99%
“…Hayden and colleagues demonstrated that the use of an infection prevention bundle that included chlorhexidine bathing and strict isolation practices in a high-CRE-burden LTACH was able to significantly reduce the rates of both new CRE acquisitions and bacteremia cases (13). Computer model estimates suggest that a coordinated regional response, compared to individual hospital actions, has the potential to reduce or even eliminate CRE transmission (10,11).…”
mentioning
confidence: 99%
“…Early identification of patients colonized with carbapenemase-producing CRE (CP-CRE) and implementation of infection prevention strategies that include strict isolation practices have the potential to significantly slow the trajectory of CP-CRE dissemination in the United States (12)(13)(14). However, such interventions critically depend on accurate and rapid identification of patients colonized or infected by CRE through laboratory testing.…”
mentioning
confidence: 99%
“…The key components of a successful hospital bundle for MDRGN are yet to be determined but have been successful at reducing nosocomial infection rates and controlling outbreaks. Most include improved hand hygiene compliance, contact precaution, control interventions cohort, staff education, and environmental disinfection [76][77][78][79][80] (Table 6). Other infection prevention strategies such as decolonization of patients by the use of daily chlorhexidine bathing have also demonstrated a reduction in the acquisition of MDR Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Other infection prevention strategies such as decolonization of patients by the use of daily chlorhexidine bathing have also demonstrated a reduction in the acquisition of MDR Gram-negative bacteria. 78 In addition, selective decontamination strategies have shown to be safe and possibly effective during therapy, but success at decolonization may favour the emergence of resistant strains and longterm effects are unclear. …”
Section: Resultsmentioning
confidence: 99%